Postural orthostatic tachycardia syndrome. Issue 981 (29th June 2007) - Agarwal, A K; Garg, R; Ritch, A; Sarkar, P
Abstract : Postural orthostatic tachycardia syndrome (POTS) is an autonomic disturbance which has become better understood in recent years. It is now thought to encompass a group of disorders that have similar clinical features, such as orthostatic intolerance, but individual distinguishing parameters—for example, blood pressure and pulse rate. The clinical picture, diagnosis, and management of POTS are discussed.